Methods for Extracellular Vesicles Isolation in a Hospital Setting - Sáenz-Cuesta, Matías; Arbelaiz, Ander; Oregi, Amaia; Irizar, Haritz; Osorio-Querejeta, Iñaki; Muñoz-Culla, Maider; Banales, Jesus M.; Falcón-Pérez, Juan M.; Olascoaga, Javier; Otaegui, David (Frontiers in Immunology, 2015)
The research in extracellular vesicles (EVs) has been rising during the last decade. However, there is no clear consensus on the most accurate protocol to isolate and analyze them. Besides, most of the current protocols are difficult to implement in a hospital setting due to being very time consuming or to requirements of specific infrastructure. Thus, our aim is to compare five different protocols (comprising two different medium-speed differential centrifugation protocols; commercially polymeric precipitation -exoquick-; acid precipitation; and ultracentrifugation) for blood and urine samples to determine the most suitable one for the isolation of EVs. Nanoparticle tracking analysis, flow cytometry, western blot, electronic microscopy and spectrophotometry were used to characterize basic aspects of EVs such us concentration, size distribution, cell-origin and transmembrane markers and RNA concentration. The highest EV concentrations were obtained using the exoquick protocol, followed by both differential centrifugation protocols, while the ultracentrifugation and acid-precipitation protocols yielded considerably lower EV concentrations. The five protocols isolated EVs of similar characteristics regarding markers and RNA concentration however standard protocol recovered only small EVs. EV isolated with exoquick presented difficult to be analyzed with western blot. The RNA concentrations obtained from urine-derived EVs were similar to those obtained from blood-derived ones, despite the urine EV concentration being 10 to 20 times lower. We consider that a medium-speed differential centrifugation could be suitable to be applied in a hospital setting due to require the simplest infrastructure and recover higher concentration of EV than standard protocol. A workflow from sampling to characterization of EVs is proposed.